Kalimāt Aʻjamiyyah fī al-Bayān al-ʻArabiy al-Mubīn - Ahmad Dardiri (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2005)
There is a difference of opinions among scholars regarding the presence of the word ‘ajam in the Quran. Some scholars deny it while some others acknowledged its existence. However, there is actually no fundamental difference between the two opinions. For initially the word is adopted from a foreign language, where the form is then changed/adjusted by the Arabs, and is spread through their conversations in the period of pre-Islam. After the Islam comes, the following words have been used as an Arabic vocabulary.